Optimization of taro (Colocasia esculenta (L.) Schott) flour substitution in tarts - Acosta, Heherson Medrano (2005)
ABSTRACT Taro (Colocasia esculenta [L.] Schott) was utilized as a raw material to produce flour by using a High Performance Dehydration System (Sandvik dryer). The dehydration procedure at 70°C was standardized by repeated production trials. The subjective and objective parameters measured revealed that the process is repeatable. The produced taro flour was employed to partially substitute all-purpose flour in making tart. Initially, a broad range of substitution levels (0%, 25%, and 40% and 55%) was used. Consumer acceptance test showed that 0% and 25% substitution were not significantly different from each other. A narrower range of substitution levels (0%, 20%, 25% and 30%) was investigated, further. Based on the results of the consumer acceptance test, it was revealed that 30% was the optimum level of substitution that is still acceptable to the consumers.